Assessment of maturity stage and stability of new Indonesian melon cultivar ‘Melona’ based on ISSR markers and morphological characteristics - ADIB FAKHRUDDIN YUSUF; ADHESTYA ALFIANI; TANTRI AJENG SALMA SALSABILA; PRIMA SEKTI KUSNANDA; INA NUR HIDAYATI; BUDI SETIADI DARYONO (Society for Indonesian Biodiversity, 2023)
Abstract. Yusuf AF, Alfiyani A, Salsabila TAS, Kusnanda PS, Hidayati IN, Daryono BS. 2023. Assessment of maturity stage and stability of new Indonesian melon cultivar ‘Melona’ based on ISSR markers and morphological characteristics. Biodiversitas 24: 308-316. Market preferences for horticultural products determine the product’s selling value and absorption. One market criterion often used for the quality of horticultural products is color and maturity level. Color differences can provide a representation of the metabolites contained in a product. This study provides a standard for assessing melons' maturity level, which will be helpful as a benchmark for Indonesian consumer acceptance. In addition, this study also provides information on the stability of the character of the new cultivar 'Melona' from several generations of crosses to obtain superior cultivars. Assessment of maturity level based on color development in 'Melona' is divided into five stages. In the first and second stage, fruit was dominated by green color with Increasing fruit volume. The color change begins in the third stage. in the third stage and the following phases, there is an increase in the accumulation of beta-carotene and characterized by the dominance of orange instead of green. Maximum ripe of ‘Melona’ is characterized by strong yellow lobes, creamy-white interlobes, and orange flesh color. A molecular analysis employing four ISSR primers (UBC-807, UBC-808, UBC-811, and UBC-824) resulted in high uniformity and low genetic variation in the hybrid and parent lines genotype. Analysis resulted a total of 42 DNA fragments with only one polymorphic DNA fragment. The polymorphic DNA fragment was 2,300 bp in size and was found in the female accession 'Melona' and the hybrid 'Melona' based on the UBC-808 primer. The numerical phenetic relationship between male, female and hybrid accession melon cultivars is very close (above 97.6%) and indicated that the melona cultivars were stable.